2013
DOI: 10.1371/journal.pone.0084643
|View full text |Cite
|
Sign up to set email alerts
|

Eat Me If You Can: Cognitive Mechanisms Underlying the Distance Effect

Abstract: Proximal objects provide affordances that activate the motor information involved in interacting with the objects. This effect has previously been shown for artifacts but not for natural objects, such as food. This study examined whether the sight of proximal food, compared to distant food activates eating-related information. In two experiments reaction times to verbal labels following the sight of proximal and distant objects (food and toys) were measured. Verbal labels included function words that were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…The bowls on the pictures were exhibited at slightly different combinations of distances to avoid the repetition of identical pictures. Whereas previous research has shown effects of stimulus distance ( Junghans, Evers, & De Ridder, 2013 ), differences employed here were much smaller (~ 10–15 cm).…”
Section: Methodscontrasting
confidence: 83%
“…The bowls on the pictures were exhibited at slightly different combinations of distances to avoid the repetition of identical pictures. Whereas previous research has shown effects of stimulus distance ( Junghans, Evers, & De Ridder, 2013 ), differences employed here were much smaller (~ 10–15 cm).…”
Section: Methodscontrasting
confidence: 83%
“…In a previous study involving food, Junghans et al (2013) showed that eating-related information was more strongly activated by the sight of proximal than distant food. Participants were shown images of proximal or distant food or other objects, followed by words relating to eating, observation, or other content.…”
Section: Introductionmentioning
confidence: 87%
“…Appropriate body-movements are not based on mere mental computations, but an organism’s functioning essentially depends on the environment surrounding it. Previous research involving a number of animal species and humans has shown that objects, including food, in the proximal environment automatically activate, and facilitate possibilities for motoric movements in interaction with the objects, so-called affordances ( Costantini et al, 2011 ; Junghans et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite participants reporting motoric difficulties with eating in the dark (Scheibehenne et al, 2010), a systematic examination and experimental variation of how the ability to maneuver in dark conditions affects consumption has been missing. Previous research has indicated that eating behaviour is influenced by accessibility of food (Wansink, Painter, & Lee, 2006), visual information about the food consumed (Wansink, Painter, & North, 2005), as well as the degree to which it yields immediate interaction such as grasping and eating (Junghans, Evers, & de Ridder, 2013). In line with this body of research, we posit that an understanding of how the ability to maneuver in dark settings influences eating behaviour is essential to ensure a holistic interpretation of the effects of food visibility on consumption.…”
Section: Introductionmentioning
confidence: 66%